Pemanfaatan ICT (Informations and Communication Technologies) dalam Pembelajaran Anak Usia Dini - Susanto, Abdi (Tarbawy : Jurnal Pendidikan Islam, 2017)
The presence of Information Communication and Technology (ICT) in Information and Communication Technology (ICT) has penetrated every area of human life, including in the world of education. The role of ICT in the world of education is very large, not only among higher education institutions but also in early childhood education. In Amendment to the 1945 Constitution article 28 paragraph 2, it is stated that every child has the right to develop themselves through meeting their basic needs, having the right to education and to benefit from science and technology, art and culture, to improve their quality of life and for the welfare of mankind In order to develop early childhood, many of us now find a variety of formal and non-formal education services. Whatever the form of service, it should pay attention to the principles of early childhood learning. In addition to paying attention to the principle of learning, the scope of material provided is also very diverse according to aspects of child development. Various media can be used from those found in the child's own body such as fingers and toes, clothing, colorful eating utensils and various sizes, beams, plants, even sophisticated multi-media (technology) must be designed according to age and needs. early childhood development. This is because in order to optimize all the potential that exists in the child. So that in turn a solid foundation will be formed in the future.